(untitled) (Academic journal Industrial Machine Building Civil Engineering, 2017)
This paper provides detailed suggestions for the process of structural reinforcement modeling by composite materials on the software package «LIRA-SAPR». It also provides the implementation of bearing capacity checks for reinforced elements on the program called «ESPRI». The article offers an algorithm for calculation of the construction objects in case of design situation changing, considering the modeling of the composite structure reinforcement. It considered the modeling process of reinforcement of structures using classical methods, such as using of metal casing. It also investigated a numerical modeling example of the frame structure reinforcement, with the selection and verification of the composite material.